Young Children Show Little Sensitivity to the Iconicity in Number Gestures. Issue 4 (2nd October 2018) - Nicoladis, Elena; Marentette, Paula; Pika, Simone; Barbosa, Poliana Gonçalves
ABSTRACT: These studies tested two questions about the developmental origins of children's sensitivity to iconicity with regard to number gestures: (1) whether children initially learn number gestures with sensitivity to the one-to-one correspondence between fingers and quantities or whether they learn them as unanalyzed symbols; and (2) whether sensitivity to iconicity increases with general cognitive development (as indexed by age) or with experience using fingers for counting. We carried out three experimental studies testing if children generalized the one-to-one correspondence in conventional number gestures to unconventional gestures. In Study 1, children between two and five years of age showed little sensitivity to iconicity, tending to be more accurate with conventional than unconventional gestures. In Study 2, we randomly assigned children to count on their fingers or to count only with words. Children with finger-counting experience did not improve in interpreting unconventional number gestures. In Study 3, we compared age-matched samples of children in school (in France) and children in daycare (in Canada). We found that schooling had little impact on children's interpretation of unconventional gestures. These results suggest that young children initially learn number gestures as unanalyzed Gestalts and only later develop sensitivity to the iconicity available in number gestures.